Spy wars moles, mysteries, and deadly games - Bagley, Tennent H. (Yale University Press, 2007)
Written by a former CIA chief of counter intelligence, this work breaks open the mysterious case of KGB officer Yuri Nosenko's 1964 defection to the United States. It guides the reader step by step through the complicated operations surrounding the Nosenko affair and shatters the comfortable version of events the CIA has presented to the public.